2016
DOI: 10.1002/anie.201609442
|View full text |Cite
|
Sign up to set email alerts
|

Selective Coke Combustion by Oxygen Pulsing During Mo/ZSM‐5‐Catalyzed Methane Dehydroaromatization

Abstract: Non‐oxidative methane dehydroaromatization is a promising reaction to directly convert natural gas into aromatic hydrocarbons and hydrogen. Commercialization of this technology is hampered by rapid catalyst deactivation because of coking. A novel approach is presented involving selective oxidation of coke during methane dehydroaromatization at 700 °C. Periodic pulsing of oxygen into the methane feed results in substantially higher cumulative product yield with synthesis gas; a H2/CO ratio close to two is the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 41 publications
2
63
0
Order By: Relevance
“…[6] There is ag rowing consensus that the active centers are monomeric or dimeric molybdenum (oxy)carbidic species which are stabilized inside the zeolite pores, while larger Mo 2 Cs pecies on the external surface are mere spectators. [10] 4) Use of oxygenpermeable membranes for ac ontrolled supply of as mall amount of oxygen for removal of coke species. [8] 2) Adsorptive or oxidative scavenging of hydrogen for the same purpose.…”
mentioning
confidence: 99%
“…[6] There is ag rowing consensus that the active centers are monomeric or dimeric molybdenum (oxy)carbidic species which are stabilized inside the zeolite pores, while larger Mo 2 Cs pecies on the external surface are mere spectators. [10] 4) Use of oxygenpermeable membranes for ac ontrolled supply of as mall amount of oxygen for removal of coke species. [8] 2) Adsorptive or oxidative scavenging of hydrogen for the same purpose.…”
mentioning
confidence: 99%
“…Ther eaction, however,i sc hallenged by ah igh-temperature endothermic nature,low C 2+ yields,and coke formation. [5] Then oncatalytic route focuses on CH 4 pyrolysis to achieve high acetylene yield, but temperatures above 1973 Kare required. [5] Then oncatalytic route focuses on CH 4 pyrolysis to achieve high acetylene yield, but temperatures above 1973 Kare required.…”
mentioning
confidence: 99%
“…2 The main product of coke removal by oxygen was CO, in good agreement with results of our recent study showing that short pulses of oxygen during the MDA reaction decrease the rate of coke deactivation. 3 Ichikawa et al observed that addition of water improves catalyst stability, attributed to steam-reforming of coke species. 4 The reverse Boudouard reaction of carbonaceous deposits with CO 2 can also improve the stability of MDA catalysts.…”
mentioning
confidence: 99%